Legal Pluralism in Canada and the Vitality of Indigenous Law - McNeil, Kent (Osgoode Digital Commons, 2025)
State law in Canada consists of the civil law in private law matters in Quebec and the common law in public law matters there and generally in the rest of the country, supplemented by legislation. Legislative authority is divided by the Constitution Act, 1867,1 between the federal government and the ten provinces. In addition, the three territories – Yukon, Northwest Territories, and Nunavut – have legislative authority that has been delegated to them by the Parliament of Canada. This federal division of powers means that there is federal law that is generally uniform throughout Canada (e.g. criminal law) and provincial and territorial law that varies from province to province and territory to territory. Quebec law varies the most because it is based on Quebec’s Civil Code and supplementary legislation.